Association between tobacco smoke exposure and constipation among American adults: a National Health and Nutrition Examination Survey - Cui, Guoce; Jiao, Xia; Wang, Zhenbiao; Zhang, Zhuhui (Frontiers in Public Health, 2025)
BackgroundStudies have shown that there is a relationship between smoke exposure and constipation. However, there are limited data on the associations between constipation and smoking or serum cotinine levels, a metabolite of nicotine commonly used as a marker of tobacco exposure.MethodsThis study thoroughly examined the cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2010. We applied multivariate logistic regression models to assess the association between tobacco smoking status, serum cotinine levels, and constipation.ResultsIn this cross-sectional study, 11,651 participants were included. The average age of the participants was 48.8 ± 17.9 years. After controlling for covariates, there was no significant relationship between serum cotinine levels, smoking status, and constipation risk. According to the categorical analysis, the incidence of constipation was 36% higher in participants with serum cotinine levels between 0.05 and 2.99 ng/mL (model 1: OR = 1.45 [1.13–1.85]; model 2: OR = 1.44 [1.12–1.83]; and model 3: OR = 1.36 [1.06–1.74]; p < 0.05) after adjusting for covariates by using the lowest levels of serum cotinine (<0.05 ng/mL) as a reference. In the non-smokers, serum cotinine levels were linearly and positively associated with the risk of constipation (p > 0.05), and the relationship between smoke exposure and constipation remained relatively stable in across all subgroups.ConclusionThe study suggests that serum cotinine levels have a promoting effect on stool frequency-related constipation in non-smokers. Therefore, avoiding passive smoking as much as possible may reduce the effect of smoke exposure on constipation and serve as a preventive measure for treatment.